Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/pmic.200401204
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and immunological studies of nucleocapsid proteins of severe acute respiratory syndrome and 229E human coronaviruses

Abstract: Severe acute respiratory syndrome (SARS) is a serious health threat and its early diagnosis is important for infection control and potential treatment of the disease. Diagnostic tools require rapid and accurate methods, of which a capture ELISA method may be useful. Toward this goal, we have prepared and characterized soluble full-length nucleocapsid proteins (N protein) from SARS and 229E human coronaviruses. N proteins form oligomers, mostly as dimers at low concentration. These two N proteins degrade rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 33 publications
9
80
0
Order By: Relevance
“…And it as has been demonstrated that these proteins can sequester the genomic RNA in such a way that host-sensing proteins do not detect it. SARS-CoV N protein is also an RNA-binding protein [29,30]. Therefore, it may be possible that N protein employs a similar mechanism to inhibit the IFN response.…”
Section: Discussionmentioning
confidence: 99%
“…And it as has been demonstrated that these proteins can sequester the genomic RNA in such a way that host-sensing proteins do not detect it. SARS-CoV N protein is also an RNA-binding protein [29,30]. Therefore, it may be possible that N protein employs a similar mechanism to inhibit the IFN response.…”
Section: Discussionmentioning
confidence: 99%
“…The self-association mechanism of the full-length HCoV-229E N protein has been previously reported [21,47]. To determine whether the C-terminal tail region (N351-389) plays an important role in the oligomerization of the C-terminal domain of the HCoV-229E N protein, the oligomerization of several regions of the C-terminal domain of the N protein were analyzed using analytical ultracentrifugation.…”
Section: Oligomerization Characterization Of the Hcov-229e Nucleocapsmentioning
confidence: 99%
“…The CoV N protein has also been shown to act as an RNA chaperone [26]. Moreover, the N protein is an important diagnostic marker and immunodominant antigen in host immune responses [21,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations